2023
DOI: 10.1038/s41427-022-00439-8
|View full text |Cite
|
Sign up to set email alerts
|

Controlled growth of a graphdiyne-Prussian blue analog heterostructure for efficient ammonia production

Abstract: Selective and efficient ammonia (NH3) production using an electrocatalytic nitrate reduction reaction (ECNtRR) under ambient conditions provides a green and promising alternative to the traditional energy-intensive Haber–Bosch process. The challenge is in design and controlled syntheses of efficient electrocatalysts with high selectivities, high NH3 yield rates (YNH3) and long-term stabilities. Here, a freestanding three-dimensional graphdiyne-hollowed FeCoNi Prussian blue analog electrode (h-FeCoNi PBA@GDY) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 65 publications
0
7
0
Order By: Relevance
“…The GNQD-Ru and GDQD-Ru were synthesized based on a two-step strategy, including the preparation of GNQD-NH 3 and GDQD-NH 3 via functionalizing GNQDs and GDQDs with amine groups, followed by the cross-linking and self-assembly of Ru-doped GNQD-NH 3 and GDQD-NH 3 by pyrolysis (see Methods), respectively. Transmission electron microscopy (TEM) analyses in Figures a and d reveal that GNQD-NH 3 and GDQD-NH 3 are well crystallized, with a basically uniform size of ∼10 nm and ∼5–8 nm, respectively. Theoretically, the decreasing sizes of GNQD-NH 3 /GDQD-NH 3 are related to the increasing concentration of the surface functional group, thus leading to a higher content of anchored Ru single atoms . X-ray photoelectron spectroscopy (XPS) analyses of the as-synthesized GNQD-Ru and GDQD-Ru present high nitrogen contents of 20.1 and 29.7 atom %, respectively (Table S1).…”
Section: Resultsmentioning
confidence: 99%
“…The GNQD-Ru and GDQD-Ru were synthesized based on a two-step strategy, including the preparation of GNQD-NH 3 and GDQD-NH 3 via functionalizing GNQDs and GDQDs with amine groups, followed by the cross-linking and self-assembly of Ru-doped GNQD-NH 3 and GDQD-NH 3 by pyrolysis (see Methods), respectively. Transmission electron microscopy (TEM) analyses in Figures a and d reveal that GNQD-NH 3 and GDQD-NH 3 are well crystallized, with a basically uniform size of ∼10 nm and ∼5–8 nm, respectively. Theoretically, the decreasing sizes of GNQD-NH 3 /GDQD-NH 3 are related to the increasing concentration of the surface functional group, thus leading to a higher content of anchored Ru single atoms . X-ray photoelectron spectroscopy (XPS) analyses of the as-synthesized GNQD-Ru and GDQD-Ru present high nitrogen contents of 20.1 and 29.7 atom %, respectively (Table S1).…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, Prussian blue analogues (PBAs) are an interesting class of intriguing candidates for next-generation electrode materials due to their physical and electrochemical properties. 10 They can be considered a type of metal−organic framework and the general formula is P a Q[Fe(CN) 6 ] b •cH 2 O, (0 ≤ a ≤ 2, b < 1). P is the insertion ion, usually K or Na (alkali metals), and Q represents the transition metal.…”
Section: Introductionmentioning
confidence: 99%
“…Nitrogen in nitrate ions has an oxidation state of +5, which can form a number of nitrogenous products in oxidation states from +3 to −3, including nitrite (+3, NO 2 – ), nitric oxide (+2, NO), nitrous oxide (+1, N 2 O), nitrogen (0, N 2 ), hydroxylamine (−1, NH 2 OH), hydrazine (−2, N 2 H 4 ), and ammonia (−3, NH 3 ). , Development of numerous electrocatalytic systems using a variety of heterogeneous catalysts including Cu, Ag, Au, Rh, Ru, Ir, Pd, Pt, etc. often converts NO 3 – to N 2 via a five-electron transfer process. Several research groups have also shown that electrochemically NO 3 – can be converted to hydroxylamine, nitrite, and hydrazine. Electrocatalytic nitrate to ammonia conversion [NO 3 – + 6H 2 O + 8e – → NH 3 + 9OH – ] via an eight-electron transfer process using metal, nonmetal, and transition-metal-based electrocatalysts would be an alternative option for next-generation ammonia production. The selectivity toward ammonia synthesis was unsatisfactory, and generally a broad range of products is obtained. This is due to the complexity of the process, strong competition from HER, and the production of various byproducts, which reduce the faradaic efficiency (FE) and selectivity of ammonia .…”
Section: Introductionmentioning
confidence: 99%